Advances in luxury brand management - Kapferer, Jean-Noël; Kernstock, Joachim, 1966-; Brexendorf, Tim Oliver, 1973-; Powell, Shaun M. (Palgrave Macmillan, 2017)
Presenting some of the most significant research on the modern understanding of luxury, this edited collection of articles from the Journal of Brand Management explores the complex relationships consumers tie with luxury, and the unique characteristics of luxury brand management. Covering the segmentation of luxury consumers worldwide, the specificity of luxury management, the role of sustainability for luxury brands and major insights from a customer point of view, Advances in Luxury Brand Management is essential reading for upper level students as well as scholars and discerning practitioners.
Conclusions and Further Research Steps.
Keywords: Luxuries -- Marketing.; Luxury goods industry.; Brand name products -- Management.; Branding (Marketing); elektronické knihy; electronic books